Embraced by the light - Eadie, Betty J. (Betty Jean), 1942-; Taylor, Curtis, 1956- (Placerville, CA : Gold Leaf Press, 1992)
The author recounts her near-death experience, recounting the miraculous visions she saw, the emotions she experienced, and how it changed her subsequent life
Keywords: Near-death experiences